PERANAN KEPOLISIAN DALAM PENCEGAHAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK DI WILAYAH HUKUM POLISI RESORT KOTA PEKANBARU - Muhammad Fathra Fahasta; Dodi Haryono; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Police have the legal legally in the form of the draft Criminal Law (KUHP) and Act No. 23 of 2002 on Child Protection, but the reality is the presence of children committing criminal offenses and recently in the form of child crime criminal act occurred pekanbaru town like, assault, sexual abuse, and drug abuse to the extent to which the role of the police in the prevention of criminal offenses committed by children in the jurisdiction of Police Resort Pekanbaru.